Níveis, tendências, distribuição espacial e determinantes sócioeconômicos da fecundidade na Região Norte - (:unkn) unknown (Universidade Federal do Amazonas, 2008)
This work intends to analyze the behavior of the fecundity in the region North from the decade of 60, when the process of transistion of the fecundity - of high for low levels - in the country is initiated. It was opted in carrying through an analysis of the relation of the levels of fecundity with the education and income of the North women. Using the data of the demographic censuses of 1991 and 2000 and of the National Research for Sample of Domiciles (PNAD) of 2006, it is made first an analysis of the evolution of the levels and standards of the fecundity from years 60 in the region North and states. After that it was possible to carry through a space analysis of the levels of fecundity in the microregions of the region North. E finally, proceeded it an analysis from the relation of the levels and etários standards of the fecundity with the education degree and familiar income of the North women. How much to the levels of fecundity of the Region North it was observed that it has a trend of convergence of the levels for lesser values each time. However, the speed of this convergence is bigger for the resident women in the urban areas. Already it is possible to verify that the North more walks each time for the standard of the too much Brazilian regions, tending to finish with the heading of region with bigger fecundity it country. It is verified that the majority of the states of the region North already meets with next levels of fecundity to the spare level. The State of the Tocantins would be the only state of the region that already possesss fecundity below of the spare level. The Amapá and Acre still are the states that present the biggest taxes of fecundity of the region. We verify that the education possesss a direct relation with the levels of fecundity of the resident women in the region North. The education, beyond making possible the woman biggest possibility to improve its social and economic conditions, is also a determinative factor of the fecundity levels. The behavior of the fecundity in accordance with the family income indicates that it has a trend of the high fecundity if to reveal in the families with inferior monthly income one wage-minimum. One expects that this work presents subsidies for the application of programs and efficient public politics that guarantee the reproductive rights and access to the reproductive health for the set of the North population.
Keywords: Fecundidade - Região Norte - Brasil; Educação e Renda - Mulheres nordestinas; Distribuição espacial e Determinantes sócioeconômicos; Space distribution and Determinative partner-economic; CIÊNCIAS SOCIAIS APLICADAS